ANALISIS PIUTANG DAGANG PADA UD. MITRA SARANA ABADI SAMARINDA - -, Ragil Suparmadi (EKONOMIA, 2014)
UD . Mitra Sarana Abadi is one equipment distributor - electronic equipment in East Kalimantan that was founded May 1st 1992 in Samarinda .Based on the overall results of the study can be addressed by looking at the results of analysis of the accounts receivable turnover rate in the first period as much as 21.65 and 16.30 in the second period , the collection of the receivable exceeds the company's policy for 14 days for 16 days and the subsequent period of 22 days , so also with the collection of accounts receivable for 19 days in the first period and 26 days in the second period, which means that the rate of turnover of accounts receivable, accounts receivable collection, and the collection of accounts receivable is not good.So based on the results of the analysis it can be concluded that the policy - a policy the company's trade receivables turnover is not optimal for uncollectible accounts receivable due . Then the hypothesis is accepted because of the level of accounts receivable turnover decreased in 2011 compared to 2010 .